Ecologia da vegetação de caatingas em diferentes substratos, Bahia, Brasil - Costa, Grênivel Mota da (2014)
The caatinga vegetation of northeastern Brazil mainly occurs in Pre-Cambrian-crystalline-derived soils and sedimentary-basin-derived sandy soils. Recent evidence has shown variations in the dynamics, structure and floristic composition of the caatinga, which justifies the need for studies focusing on different substrates. A floristic study of the caatinga ecoregions Depressão Sertaneja Meridional and Raso da Catarina in the municipality of Tucano, Bahia, Brazil, is of special interest because both substrates occur in a local scale, letting the opportunity to broaden our knowledge on ecological heterogeneity within the Caatinga biome. In the current study we carried out a floristic survey of 14 sites distributed throughout the ecoregions of caatinga in Tucano. We found high species diversity in the caatingas of Tucano when compared to other areas in northeastern Brazil. A total of 451 species, 288 genera, and 82 families were collected. The most species rich families are Leguminosae and Euphorbiaceae. There occur 226 species in the sites on crystalline basement, whereas 284 species were collected in the sandy areas. The ecoregions were only 13% similar in floristic composition. We found strong differences between the ecoregions with respect to floristic composition and predominant plant habit as proxy for phytophysiognomy. Overall, our results reinforce the hypothesis of two distinct biotas that assembly the caatinga dry woodlands.